Erişkin hastalarda nonkonvulsif status epileptikus: Tanı ve tedavi yaklaşımı - (:unkn) unknown (My University, 1996)
Nonkonvülsif status epileptikus (NKSE) tüm status epileptikusların %20’sini oluşturur. Tanı ve tedavi geciktirildiğinde NKSE yüksek morbidite ve mortaliteye neden olmaktadır. Tedavide ilaç seçimi için parsiyel ya da jeneralize ayrımı önem taşımaktadır. Bu yazıda klinik ve EEG bulguları ile tanımlanmış iki kompleks parsiyel status epileptikus (KPSE) ve bir primer jeneralize status epileptikus vakası sunulmuştur. İki hastanın etiyolojisinde serebrovasküler olay yer almaktayken, üçüncü hastada patolojik bulgu saptanmadı. NKSE ve özellikle KPSE selim gidişli tablolar değildirler ve düşünülenden daha sık olarak görülmektedirler. Morbidite ve mortalite nöbetlerin tipi ve süresi, ayrıca altta yatan neden ile değişmektedir. Bu hastalarda erken tanı ve tedavi klinik gidişi belirlemekte ve bu nedenle önem taşımaktadır.

Nonconvulsive status epilepticus (NCSE) accounts for approximately 20% of status epilepticus. The diagnosis and treatment of NCSE may sometimes be delayed and serious morbidity and mortality could occur. A differentiation between partial and generalized forms is important for the choice of prophylactic drug therapy. We described three patients two of whom had complex partial status epilepticus (CPSE) and one with primary generalized status epilepticus as documented by clinical and EEG findings with seizures persisting more than one hour. The underlying pathologies were vascular diseases in two of them whereas no abnormality was detected in the third patient. NCSE and especially CPSE are not benign entities and are more common than is appreciated. The morbidity and mortality could change according to the course of seizures ad the etiology of the disorder precipitating SE. Early treatment may improve the neurologic outcome of patients. Consequently, early diagnosis and treatment of NCSE deserve greater attention.
Nonconvulsive status epilepticus in adult patients: Diagnosis and treatment
Keywords: Hematoloji; Pediatri; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme